Liver abscess: presentation and an assesment of the outcome with various treatment modalities - P. N., Sreeramulu; Swamy, Srinivasan Dorai; N., Vikranth Suresh; S., Suma (International Surgery Journal, 2019)
Background: Liver abscess is a disease of frequent occurrence which is important in the differential diagnosis of upper abdominal and right lower respiratory tract diseases. Liver abscess are space occupying lesion in liver which has a higher incidence of mortality and morbidity. The aim is to study the clinical presentation and compare the outcomes of various treatment modalities. Methods: A Retrospective Study was conducted over a period of 3 years from November 2016 to October 2019, in tertiary care centre, R. L. Jalappa hospital, Tamaka, Kolar, Karnataka, India. 46 cases of liver abscesses were studied. Complete clinical details about the clinical presentation of the cases, investigative work up and treatment modalities adopted were collected. The associated morbidity and mortality of all patients were reviewed. Results: In our study, the mean age was 49.5 years which included male patients most commonly. Pyogenic liver abscess was more common than amoebic liver abscess. Right lobe of the liver was most commonly involved. The common treatment modality was continuous drainage of the abscess cavity by the percutaneous insertion of a pig tail catheter. Surgical intervention for the rupture was done in one patient. Conclusions: In our experience of managing liver abscess, pyogenic liver abscess involving right lobe of the liver was common with the presentation of upper abdominal pain, high grade fever with chills and tender hepatomegaly. Ultrasound abdomen is very useful investigative tool in diagnosis and also in intervention and in the follow up of the condition and to evaluate progression or resolution.